Tanzania Towards Industrialization; Kilimo Kwanza Policy Towards Economic Growth and Self-Sustaining - Mwaisakila, Stephen Richard; Matemani, James Kalimanzila (Jurnal Magister Administrasi Publik, 2021)
Since independence, agriculture has been the backbone of Tanzania's economy. Factors like good climatical condition, arable land, and manpower give the advantage to do well in agriculture as a tool for economic growth and self-sustaining. Despite having a good agriculture policy (Kilimo Kwanza), the country is not doing well in utilizing its full potential in the agriculture sector. This is due to several challenges like the political economy of agriculture, budget bias (constraints) against agriculture, and market bias against agriculture. To solve those problems and make this policy and agriculture more sustainable in achieving economic growth, industrialization (Tanzania ya Viwanda), and self-sustaining, this study is recommending the government to make some adjustments in the policy to match with the annual budget trends to avoid deficits. Moreover, the government should provide education to increase perceptions to the decision-makers about the importance of agriculture in the economy to reduce the biases on agriculture in their decision-making processes.